The prevalence of opportunistic infections and malignancies in autopsied patients with human immunodeficiency virus infection in Japan - Katano, Harutaka (BioMed Central, 2014)
BACKGROUND: Opportunistic infections and malignancies such as malignant lymphoma and Kaposi sarcoma are significant complications of human immunodeficiency virus (HIV) infection. However, following the introduction of antiretroviral therapy in Japan in 1997, the incidence of clinical complications has decreased. In the present study, autopsy cases of HIV infection in Japan were retrospectively investigated to reveal the prevalence of opportunistic infections and malignancies. METHODS: A total of 225 autopsy cases of HIV infection identified at 4 Japanese hospitals from 1985–2012 were retrospectively reviewed. Clinical data were collected from patient medical records. RESULTS: Mean CD4 counts of patients were 77.0 cells/μL in patients who received any antiretroviral therapy during their lives (ART (+) patients) and 39.6 cells/μL in naïve patients (ART (−) patients). Cytomegalovirus infection (142 cases, 63.1%) and pneumocystis pneumonia (66 cases, 29.3%) were the most frequent opportunistic infections, and their prevalence was significantly lower in ART (+) patients than ART (−) patients. Non-Hodgkin lymphoma and Kaposi sarcoma were observed in 30.1% and 16.2% of ART (−) patients, and 37.9% and 15.2% of ART (+) patients, respectively. Malignant lymphoma was the most frequent cause of death, followed by cytomegalovirus infection regardless of ART. Non-acquired immunodeficiency syndrome (AIDS)-defining cancers such as liver and lung cancer caused death more frequently in ART (+) patients (9.1%) than in ART (−) patients (1.5%; P = 0.026). CONCLUSIONS: The prevalence of infectious diseases and malignancies were revealed in autopsy cases of HIV infection in Japan. The prevalence of cytomegalovirus infection and pneumocystis pneumonia at autopsy were lower in ART (+) patients than ART (−) patients. Higher prevalence of non-AIDS defining malignancies among ART (+) patients than ART (−) patients suggests that onsets of various opportunistic infections and malignancies should be carefully monitored regardless of whether the patient is receiving ART.